Urgensi Undang-Undang Sistem Peradilan Pidana Anak - Suhadi Suhadi (UNISSULA Semarang, 2020)
There are some basic things in the child criminal justice system as stipulated by Law Number 11 Year 2012 on Child Criminal Justice System (hereinafter referred to as SPPA Law), among others are age limit of detention for children above 14 years, age limit of criminal responsibility of child of 14 years - 18 years and the adoption of a diversionary effort, namely the settlement of a Child case, especially a child in conflict with the law of the settlement through a criminal court, is diverted beyond the criminal court. Diversi is carried out at all levels of criminal justice at the stage of investigation, prosecution and examination in court.The Criminal Justice System of the Child is the whole process of settling the Child's case against the law, from the investigation stage to the guidance stage after the crime. The Criminal Justice System is specifically implemented under the SPPA Act. The Urgency Act of SPPA is mandated restorative justice (restorative justice) and the settlement of cases outside the court or called diversiatkan.The SPPA Act in its implementation in the field is still not supported by adequate infrastructure facilities and infrastructures as mentioned therein, such as the Provisional Child Care Institution (LPAS), Lembaga Pembinaan Khusus Anak (LPKA), Penitentiary (BAPAS), Social Welfare Implementing Agency (LPKS) ). Ideally a legislation should be issued with adequate facilities and infrastructure, so the government should immediately improve the necessary facilities and infrastructure.Keywords: Urgency, Child Criminal Justice System